한국 엘리트 양궁선수들의 성별과 부상, 통증 경험에 따른 상지의 관절위치 감각과 힘감각, 경기력 수준의 차이 - 김문교; 김선엽 (대한정형도수물리치료학회지, 2021)
Objective: The purpose of this study was to examine the differences in joint position sense (JPS), force sense (FS), and performance level of the upper extremities according to the injury and pain experiences of Korean elite archers. Methods: A total of 15 subjects were briefed about the purpose of this study and agreed to participate voluntarily. JPS was evaluated using the laser-point attached to the wrist while aiming at the target. The difference when relocating while aiming was used as JPS factor. FS was evaluated using load cell through reproduces same muscle strength. Fear-Avoidance Beliefs Questionnaire (FABQ) was used to evaluate psychosocial factors, Kerlan-Jobe Orthopedic Clinic overhead athlete scores (KJOC) and numerical rating scale (NRS) was used to evaluate pain. and performance was evaluated by tournament match score. Results: There is a strong correlation between the current pain and KJOC. Moreover, moderate correlation between KJOC and FABQ also current pain and both upper trapezius and lower trapezius in elite archers. The mean (SD) between groups based on current pain display relatively large margin in force sense than without pain group. The result presents that there is a significant difference in performance and pain. There is a significant difference in the force sense of the upper and lower trapezius and pain. Conclusions: Result present there is a significant difference in functional level in the average comparison between groups according to the presence of absence of current pain. There is a significant difference in the force sense of the upper trapezius as well as lower trapezius and without pain group present a relatively low joint position sense error compared to the groups.